PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT ERAMART GROUP DI SAMARINDA - Fathullah (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2022)
This study aims to determine the effect of reward and punishment on employee performance at PT Eramart Group in Samarind. This study uses two independent variables, namely Reward and Punishment with one dependent variable, namely Employee Performance. After reviewing the literature and the field and formulating hypotheses. The data in this study were collected through distributing questionnaires to 50 respondents as the research sample. The sampling technique in this study used a Questionnaire and Literature Study. The data analysis method used is quantitative analysis, namely Instrument Test, Multiple Linear Regression Analysis, Classical Assumption Test, Correlation Test, Hypothesis Testing and Coefficient of Determination. Based on data analysis, the results showed that the variables of reward and punishment had a significant effect on employee performance either partially or simultaneously